Caracterização de reservatórios turbidíticos através de modelagem de propriedades elásticas: uma aplicação na Formação Calumbi, bacia de Sergipe- Alagoas, Brasil - Oliveira, Leonardo Barbosa de (2020)
Sandy channelized reservoirs in deep water environments are of great importance for oil exploration and production as they can constitute important oil reservoirs. The twodimensional nature of the outcrops described in the literature and the local nature of the information acquired through wells are limiting factors for the adequate characterization of this type of sedimentary environment and its heterogeneities. The absence of information between the points sampled by wells in oil reservoir is usually overcome by using 3D seismic data. Geological modeling mitigates the effects of low seismic resolution and can be optimized regarding the spatial distribution of rock properties by incorporating inverted seismic volumes that have data throughout all the geological layers. This study presents a synthetic modeling of elastic properties associated with physical properties to assess and optimize the geostatistical modeling performed in real data from turbiditic reservoirs in the Maastrichtian section of the Calumbi Formation, Sergipe Sub-basin, Brazil. Geomorphological and geological aspects, described in the literature and in similar outcrops in the Alagoas Sub-basin, associated with their responses due to their compressional velocities, shear velocities, densities, and thicknesses, were successively tested to reduce the uncertainty in the spatial distribution between the points that present high vertical-resolution data. The results obtained show that the variations of the P and S waves are the main influences on the seismic signal and on the differences between impedance P and S attribute. An equation allowed to model the effects of these attributes and, thus, to implement corrections in the geometric and faciological characteristics of the evaluated rocks.